Management Assistance and Product Quality Optimization for Ukhti Pizza MSMEs: Efforts to Increase the Competitiveness of Micro-Businesses in Kediri - Mirhamida Rahmah; Dinda Fatmah; Chamdan Purnama; Zakiyah Zulfah Rahmah; Chairul Anam (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2026)
Business management mentoring and product quality improvement are strategic efforts to support the development of MSMEs to enable them to compete in an increasingly competitive market. This community service activity was carried out at the Pizza Ukhti MSME in Kediri, with the aim of improving managerial capacity and product quality. The methods used included observation, simple financial record-keeping training, product quality improvement workshops, packaging design mentoring, and implementation monitoring for 1-2 weeks. The results of the activity showed an increase in MSME owners' understanding of business management, improvements in more efficient production processes, consistent product quality, and more attractive packaging. This activity also increased the confidence of business owners in running their businesses independently and professionally. This mentoring based on a practical and sustainable approach is expected to be replicated in other MSMEs to support sustainable local economic empowerment.